2019
DOI: 10.3390/agronomy9090488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Tillage and Crop Sequence on Grain Yield and Quality of Durum Wheat in Mediterranean Areas

Abstract: Conservation agriculture (CA) can be very strategic in degradation prone soils of Mediterranean environments to recover soil fertility and consequently improve crop productivity as well as the quality traits of the most widespread crop, durum wheat, with reference to protein accumulation and composition. The results shown by two years of data in a medium long-term experiment (7-year experiment; split-plot design) that combined two tillage practices (conventional tillage (CT) and zero tillage (ZT)) with two cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 61 publications
(69 reference statements)
3
23
0
1
Order By: Relevance
“…Hountongninou (2016) reported that tillage does not significantly affect maize grain yield and justified this by the sandy-clayey texture of its study site, which provides a similar environment under plowing. Although NT is recognized as one of the Conservation Agriculture practices (Lal, 2004;Reicosky and Saxton, 2007;Martínez et al, 2008;Tabaglio et al, 2009;Kolb et al, 2012;Soane et al, 2012;Fiorini et al, 2018), its adoption requires a transition phase (on average 7-8 years), characterized by higher annual weed and disease pressures, slow rebuilding aggregates in soil, and lower and variable yields (Knowler and Bradshaw, 2007;Pagnani et al, 2019). However, as outlined in Sharma and Abrol (2005), soil types react differently to the same tillage method.…”
Section: Discussionmentioning
confidence: 99%
“…Hountongninou (2016) reported that tillage does not significantly affect maize grain yield and justified this by the sandy-clayey texture of its study site, which provides a similar environment under plowing. Although NT is recognized as one of the Conservation Agriculture practices (Lal, 2004;Reicosky and Saxton, 2007;Martínez et al, 2008;Tabaglio et al, 2009;Kolb et al, 2012;Soane et al, 2012;Fiorini et al, 2018), its adoption requires a transition phase (on average 7-8 years), characterized by higher annual weed and disease pressures, slow rebuilding aggregates in soil, and lower and variable yields (Knowler and Bradshaw, 2007;Pagnani et al, 2019). However, as outlined in Sharma and Abrol (2005), soil types react differently to the same tillage method.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed that tillage did not substantially affect GPC in either year, except GPC under NT was significantly higher than under RR in 2017. According to the findings of Pagnani et al [51], tillage significantly influenced N accumulation and remobilization, while greater N remobilization from vegetative organs to grains was the critical factor that achieved a higher GPC. Therefore, it is inferred that the interaction of tillage and soil moisture affects N absorption and remobilization, which collectively restrict grain yield and protein formation.…”
Section: Discussionmentioning
confidence: 94%
“…Although tillage has been shown to greatly affect N absorption and remobilization 32 , the difference in N efficiency among the tillage methods can depend on soil environmental conditions. Rial-Lovera et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that water-saturated soil reduces tiller number per seedling an d inhibits root and shoot growth, affecting nutrient absorption and photosynthesis [28][29][30][31] . www.nature.com/scientificreports/ Although tillage has been shown to greatly affect N absorption and remobilization 32 , the difference in N efficiency among the tillage methods can depend on soil environmental conditions. Rial-Lovera et al 33 reported that tillage influenced N use efficiency in a humid growing season.…”
Section: Discussionmentioning
confidence: 99%